REVISITING SELF-DETERMINATION CONFLICTS IN INDONESIA: AN INTERNATIONAL LAW PERSPECTIVE - Kadir, M. Yakub Aiyub (UI Scholars Hub, 2015)
Indonesia is a former Dutch colony which declared its independence on August 17, 1945. However, it was not internationally recognised until December 27, 1949, when the Netherlands formally transferred the sovereignty of the Dutch East Indies to a new political entity called ‘Indonesia’ at the Round Table Conference in the Hague. This occasion marked the political union of all diverse kingdoms and regional communities spread over the Indonesian archipelago. This step has been frequently associated with the global spirit of many other countries around the world to gain independence from Western colonisers and with the international principle of self-determination. However, the relationship between the central government in Java and some regional communities has been fluctuating for decades after the independence. This paper examines three conflicts over the rights of self-determination in in three areas in Indonesia by reflecting on the historical background of Indonesia’s struggle for self-determination. Besides that, it also seeks to demonstrate the way Indonesia’s integrity has been negotiated to accommodate internal and external forces to achieve self-determination from international law perspective. Furthermore, this paper also contributes to the scholarly discussion on the concept of self-determination and the conflicts that it caused in Indonesian context, while also proposing some insights into the efforts to preserve Indonesia’s unity and integrity for years to come.